Teachers’ Strategies and Challenges in Implementing Strategies to Alleviate Students’ Speaking Anxiety - Muqorrobin, Muhammad; Suryati, Nunung; Wulyani, Anik Nunuk (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2025)
Foreign language anxiety (FLA) is one of the primary sources inhibiting students' speaking skill development. Previous studies explored the triggering factors of FLA and the strategies for alleviating students’ speaking anxiety. However, studies focusing on teachers’ challenges in implementing the strategies have yet to be conducted. To address the existing gap, this study aims to explore strategies teachers implemented in reducing speaking anxiety and challenges in implementing the strategies. Using narrative inquiry as a research design, this study used semi-structured interviews to collect data from two English department lecturers who are teaching in a state university in Indonesia and possess some knowledge and experience in dealing with anxious students in their speaking classes. The findings revealed that teachers’ lenience toward students’ mistakes helped reduce fear of negative evaluation, creating a comfortable atmosphere that fostered confidence and participation, and peer/group activities encouraged collaborative learning and reduced performance pressure. However, the teachers encountered difficulties maintaining students’ motivation, as learners often lost enthusiasm over time despite initial encouragement; addressing deeply rooted anxiety that had developed from repeated negative learning experiences; and managing time constraints that limited opportunities to implement interactive activities and provide individualized support effectively. These findings provide teachers with a comprehensive understanding of the dynamics of the issue in addressing students’ speaking anxiety, which consequently grants them extensive insights to design proper strategies that possibly maximize their effectiveness in reducing students’ FLA.